A comprehensive approach of groundwater vulnerability and potentiality assessment of Melaka catchment in Malaysia / Md. Imran Hosen - Md. Imran, Hosen (2012)
maps by ArcGIS software. The GIS is very important and effective tool for handling a large amount of geological and hydrogeological data within short time and minimal error. Pumping test data are collected from 210 shallow and 17 deep boreholes to get well inventory information. Analysis of these data confirmed that the aquifers consisting of schist, sand, limestone as well as volcanic rocks are the most productive for groundwater in the State of Melaka. The term ‘aquifer productivity’ represents the potential of an aquifer to sustain various levels of borehole supply. The aquifer productivity map is classified into three categories namely;- high (>12m3/h), moderate (3.6-12 m3/h) and low (<3.6 m3/h) based on the discharge capacity. The groundwater potentiality of the study area is 35% low, 57% moderate and 8% high. Seven thematic maps defining;- depth to water table, net recharge, aquifer media, soil media, topography, impact of vadose zone and hydraulic conductivity are generated and integrated to generate the final DRASTIC vulnerability map. The map is then overlaid on the additional land use map to generate the risk map, which method is called Modified DRASTIC method. Both methods have been validated using groundwater quality data. The vulnerability map are classified into three categories namely;- high (>159), moderate (120-159) and low (80-119). The DRASTIC vulnerability map shows that an area of 11.02% has low vulnerability, an area of 61.53% has moderate vulnerability and 23.45% of the area has high vulnerability in the Melaka State. On the other hand, risk map indicates that 14.40% of the area is low vulnerability (100-139), 47.34% moderate vulnerability (140-175) and 38.26% high vulnerability (>175) in the study area. The most vulnerability is seen around Melaka, Jasin and Alor Gajah City of Melaka. The 52 shallow and 14 deep borehole groundwater samples are analyzed for water quality. The analysis results indicate that groundwater quality is satisfactory for drinking and other purposes, however turbidity, total dissolved solids, iron, chloride and cadmium values are exceeded the limit of the drinking water quality standard in very few cases. The ranges of pH are 4 - 8.2 for shallow and 5.2 - 8.1 for deep boreholes. Therefore, groundwater in the State of Melaka can be used for drinking and other purposes, in which some major treatments are recommended in few cases.